PENGEMBANGAN PRODUK BERSAMA PENGANYAM TOPI BAMBU DESA RANCAKALAPA DAN PT.POLYMINDO PERMATA DENGAN PENDEKATAN DESAIN SOSIAL - Gumulya, Devanny; Ho, Yunita (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Living 24 kms from our University were bamboo hat weavers. The weavers mostly are elderly women. They have been weaving since age of 13 and the skill is passed down from generation to generation. To weave a hat, it takes two days and the weavers get pay 10.000-12.000 rupiah for the hat. This reality saddens UPH’s team, the hardwork isn’t valued. Therefore, they can’t see this as a serious job, their main job is farming. The youngsters are not interested to become a weaver and choose other job, so the remaining weavers mostly are old lady. On the other hand, PT. Polymindo Permata, a company producing weaving goods made from high density polyethylene located in Jatake with commercial name Viroforms. This is a project that tries to connect these two stakeholders through product development project with social design approach. . It emphasizes the intense interaction between the stakeholders in a co-creation activities resulted in intense workshop between the academic team, bamboo hat weavers and PT. Polymindo Permata. The weavers in Rancakalapa train PT. Polymindo Permata’s weavers how to make bamboo hat from HDPE plastic. UPH’s team give the design, The goal of this activity is to preserve the craftsmanship of bamboo hat weaving technique by applying this to other material, so that the technique can be carried on, before these weavers become more old and the crafts extinct.